The Role of Job Satisfaction in Mediating Career Development, Rewards, and Employee Well-Being on Employee Performance - Fitriani, Yani; Wulansari, Puspita (International Journal of Indonesian Business Review, 2026)
Purpose – This study aims to examine the effect of career development, rewards, and employee welfare on employee performance through job satisfaction as a mediating variable at PT Infomedia Nusantara. Methodology/approach – This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 163 employees of PT Infomedia Nusantara selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. Findings – The results indicate that rewards and employee welfare have a positive and significant effect on job satisfaction, while career development has no significant effect on job satisfaction. Job satisfaction was found to have a positive and significant effect on employee performance. Furthermore, job satisfaction mediates the relationship between rewards and employee performance as well as between employee welfare and employee performance. However, job satisfaction does not mediate the relationship between career development and employee performance. Novelty – This study contributes to the human resource management literature by examining the mediating role of job satisfaction in the relationship between career development, rewards, employee welfare, and employee performance within the Business Process Outsourcing (BPO) industry. The findings reveal that rewards and employee welfare are more influential factors in enhancing job satisfaction and employee performance than career development, providing new insights for organizations in designing effective human resource management strategies